EVALUATION OF THE SHADOW ECONOMY AND ITS IMPACT ON SOCIO-ECONOMIC DEVELOPMENT - Гірна, Олександра; Карпяк, Ілона (Socio-economic relations in the digital society, 2019)
The shadow economy includes all market-based legal production of goods and services that are deliberately concealed from public authorities. The shadow economy is presented in all, without exception, the economic systems of the world. However, an increase in the share of the shadow economy creates significant obstacles to growth in the economic and social spheres, competitiveness and integration of the country into the international economic space. The study of the scale of shadowing is a complex task that requires a large number of different methods. This is due to the fact that the shadow economy is hidden and manifests itself differently depending on the sphere of functioning, which makes it difficult to estimate its share in the national economy. The paper focuses on the identification of the advantages and disadvantages of methods for assessing the level of the shadow economy and quantitative analysis of the sensitivity of the social and economic development of national economies to the effects of the shadow economy. The work has statistically confirmed the conclusion that low levels of the shadow economy are fixed in developed countries, while poor countries have predominantly extremely large shares of the shadow sector of the economy. Correlation-regression analysis showed that among the indicators of social and economic development of countries, one of the most sensitive to the negative impact of the level of the shadow economy of the previous period is the total domestic credit to the private sector. It is shown that on average if the shadow economy of one country is 10% higher than the other, then government spending on education of the first country will be lower by 0,3% of GDP; loans to the private sector less - 21% of GDP; per capita electricity consumption is less than 2000 kW; overall life expectancy is less than 3 years compared to the other country; inflation is expected to be 0,6% higher, instead.
Keywords: shadow economy; developed countries; developing countries; statistical distribution; correlation-regression analysis